In vitro toxicological characterisation of the antifungal compound soybean toxin (SBTX). (June 2020) - Arantes, Mariana Reis; Peijnenburg, Ad; Hendriksen, Peter J.M.; Stoopen, Geert; Almeida, Thiago Silva; Souza, Terezinha Maria; Farias, Davi Felipe; Carvalho, Ana Fontenele Urano; Rocha, Talita Magalhães; Leal, Luzia Kalyne Almeida Moreira; Vasconcelos, Ilka Maria; Oliveira, Jose Tadeu Abreu
Abstract: Soybean toxin (SBTX) is a protein isolated from soybean seeds and composed of two polypeptide subunits (17 and 27 kDa). SBTX has in vitro activity against phytopathogenic fungi such as Cercospora sojina, Aspergillus niger, and Penicillium herguei, and yeasts like Candida albicans, C. parapsilosis, Kluyveromyces marxiannus, and Pichia membranifaciens . The present study aimed to analyze in vitro whether SBTX causes any side effects on non-target bacterial and mammalian cells that could impede its potential use as a novel antifungal agent. SBTX at 100 μg/mL and 200 μg/mL did not hinder the growth of the bacteria Salmonella enterica (subspecies enterica serovar choleraesuis ), Bacillus subtilis (subspecies spizizenii ) and Staphylococcus aureus . Moreover, SBTX at concentrations up to 500 μg/mL did not significantly affect the viability of erythrocytes, neutrophils, and human intestinal Caco-2 cells. To study whether SBTX could induce relevant alterations in gene expression, in vitro DNA microarray experiments were conducted in which differentiated Caco-2 cells were exposed for 24 h to 100 μg/mL or 200 μg/mL SBTX. SBTX up-regulated genes involved in cell cycle and immune response pathways, but down-regulated genes that play a role in cholesterol biosynthesis and platelet degranulation pathways. Thus, although SBTX did not affect bacteria, nor induced cytotoxity in mammalian cells, it affected some biological pathways in the human Caco-2 cell line that warrants further investigation. Highlights: SBTX is an antifungal protein from soybean seeds. SBTX is not harmful to erythrocytes and neutrophils. SBTX up-regulated genes involved in cell cycle and immune response pathways. SBTX down-regulated genes involved in cholesterol biosynthesis. SBTX down-regulated genes involved in platelet aggregation/blood coagulation.